1977
DOI: 10.1002/eji.1830071011
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive factor(s) specific for L‐glutamic acid50‐L‐tyrosine50 IV. In vitro activity and immunochemical properties

Abstract: The responsiveness of BALB/c spleen cells to the terpolymer L-glutamic acid60-L-alanine30-L-tyrosine10 (GAT), the copolymer of L-glutamic acid50-L-tyrosine50 (GT) and the corresponding complexes with methylated bovine serum albumin (MBSA) has been studied in vitro in a modified Mishell-Dutton culture system. Cultures of BALB/c spleen cells respond to GAT, GAT-MBSA and GT-MBSA over a wide dose range. Contrary to in vivo findings BALB/c spleen cell cultures respond to GT in vitro although in a much narrower dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In any event, the KLH-TsF reported in this paper resembles other antigen-specific T cell factors with suppressor function reported by Theze et al (2), and Kontiainen et al (5), and with helper function as described by Taussig et al (16), Isac et al (17), and Tokuhisa et al (18). In particular, the antigen-specific helper T cell factors have also demonstrated that they have the antigen-binding moiety and the I-A-encoded determinants.…”
Section: Resultssupporting
confidence: 85%
“…In any event, the KLH-TsF reported in this paper resembles other antigen-specific T cell factors with suppressor function reported by Theze et al (2), and Kontiainen et al (5), and with helper function as described by Taussig et al (16), Isac et al (17), and Tokuhisa et al (18). In particular, the antigen-specific helper T cell factors have also demonstrated that they have the antigen-binding moiety and the I-A-encoded determinants.…”
Section: Resultssupporting
confidence: 85%
“…Very recently, the ability of GAT-Ts to suppress nonresponder T cell proliferative responses to GAT after GAT-MBSA priming has also been used for studying suppression in this model [66]. The work ofTada et al [131] led to attempts to produce GAT and GT-TsF by sonication of spleen and thymus cells containing active T s. Such extracts did suppress GAT-MBSA or GT-MBSA responses of syngeneic mice, and were also active in vitro, permitting easy assay [69,70,147,150]. This antigen does not lead to responses in any tested inbred mouse strain, although it is immunogenic in an outbred line.…”
Section: B Studies On Tsf Specific For Polypeptides Antigens Under Imentioning
confidence: 99%
“…The genes controlling the development of GT-specifi c suppressor T cells mapped in the I region and behaved as complementing genes in both the cis and trans confi guration (73). As in the case of GAT-specifi c suppressors, lysis of GT-suppressor T cells yielded a GT-specifi c factor capable of suppressing GT-MBSA responses (74). In more recent experiments with this system, Vidovic et al investigated the ability of GT to initiate T cell proliferative responses rather than antibody production in inbred strains of mice; they observed that some of the suppressor haplotypes we had identified, i.e.…”
Section: The Generation Of Alloreactivity (1976-1978) the Expansion Omentioning
confidence: 98%